2014
DOI: 10.1017/s1368980014000111
|View full text |Cite
|
Sign up to set email alerts
|

Capturing changes in dietary patterns among older adults: a latent class analysis of an ageing Irish cohort

Abstract: Objective: Data-driven approaches to dietary patterns are under-utilized; latent class analyses (LCA) are particularly rare. The present study used an LCA to identify subgroups of people with similar dietary patterns, explore changes in dietary patterns over a 10-year period and relate these dynamics to sociodemographic factors and health outcomes. Design: The 1998 baseline and 2008 follow-up of the Cork and Kerry Diabetes and Heart Disease Study. Diets were assessed with a standard FFQ. LCA, under the assumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 50 publications
3
46
1
Order By: Relevance
“…Our findings of higher tracking for the “Vegetarian-style” dietary pattern, representing a healthy diet, and lower tracking for the “Western-like” dietary pattern, representing an unhealthy diet, are in line with other studies implying that healthy dietary habits are more stable over time [ 7 , 10 , 22 , 23 , 26 , 27 ]. However, some investigators reported a higher stability for the Western/unhealthy dietary pattern compared to the healthy dietary pattern [ 8 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of higher tracking for the “Vegetarian-style” dietary pattern, representing a healthy diet, and lower tracking for the “Western-like” dietary pattern, representing an unhealthy diet, are in line with other studies implying that healthy dietary habits are more stable over time [ 7 , 10 , 22 , 23 , 26 , 27 ]. However, some investigators reported a higher stability for the Western/unhealthy dietary pattern compared to the healthy dietary pattern [ 8 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, it appears unlikely that the observed attenuation is caused by a change in diet, as little changes in dietary patterns are seen in adulthood while aging. 21 The observed decreased risk of colon cancer with increased consumption of cabbage (analyzed as continuous variable) may be explained by the anticancer effects attributed to glucosinolates. 22 However, most prospective cohort studies have until now not reported inverse associations between consumption of cruciferous vegetables and CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The FFQ selected was a version of that used by the European Prospective Investigation into Cancer (EPIC) study 27 which had been amended for use in the Irish population. 28 Habitual dietary intake was determined by assessing the intake of 147 foodstuffs, the frequency of intake being established using 10 categories ranging from 'never' to '6 times a day or more'. The frequency categories were converted to their proportion of a single daily serving i.e.…”
Section: Dietary Phylloquinonementioning
confidence: 99%